The role of e-learning in educational institutions compared to traditional education - an applied study at the Technical Institute in Diwaniyah - زكي محمد عباس, (Iraqi Journal for Administrative Sciences, 2025)
The world is witnessing today a shift unprecedented in the world of information and communication technology and represents a real revolution called the revolution of information and the Internet making the world think seriously about how to deal and take advantage of them to serve all communities, including educational institutions through keep pace with these technological developments of using computers and the Internet, which have created a kind of education is e-learning .. The success of e-learning depends on the optimal use of the latest methods and techniques appropriate to meet the requirements of modern education and cope with the rapid technological advances at a rapid pace. I have taken such an educational institution of universities and institutes to reduce the gap of their use of traditional education and the move towards promoting e-learning as a strategic option towards development. This study highlights the interest in Iraqi universities, including the Board of Technical Education - Technical Institute in Diwaniya, the pursuit of providing a learning environment based e-learning, where I took a sample of 48 students and a student at the Institute have been distributed form questionnaire on the two scientists are the accounting department, which supports e-learning and Material Management Department, which relies traditional education by 22 students each. Was the use of statistical analysis (statistical analysis differential) to identify the priority of any two systems of the educational process in the scientific sections and based on the results of the analysis of the recommendations was raised